2004
DOI: 10.1210/jc.2003-031121
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Resistin Concentrations Measured by Enzyme-Linked Immunosorbent Assay Using a Newly Developed Monoclonal Antibody Are Elevated in Individuals with Type 2 Diabetes Mellitus

Abstract: Resistin is an adipocyte-derived peptide that might play a role in obesity and insulin resistance. However, its role in humans is largely unclear. Although many studies have measured the expression of human resistin in tissues, the circulating concentrations of resistin and its relation to metabolic parameters in humans are unknown. We developed an ELISA for human resistin and measured plasma concentrations in aged individuals with or without type 2 diabetes mellitus. To validate the results of plasma resistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
116
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 29 publications
(39 reference statements)
20
116
2
1
Order By: Relevance
“…Although data suggest that resistin levels are elevated in subjects with type 2 diabetes mellitus, 22 previous data in reference to resistin and NAFLD are conflicting. Resistin levels have been shown to be higher in patients with high grade steatosis compared with low grade steatosis 23 and are related to the histopathologic severity of disease.…”
Section: Discussionmentioning
confidence: 93%
“…Although data suggest that resistin levels are elevated in subjects with type 2 diabetes mellitus, 22 previous data in reference to resistin and NAFLD are conflicting. Resistin levels have been shown to be higher in patients with high grade steatosis compared with low grade steatosis 23 and are related to the histopathologic severity of disease.…”
Section: Discussionmentioning
confidence: 93%
“…The major risk factors of type 2 diabetes include obesity and insulin resistance with associated impaired secretion of various adipokines (Youn et al 2004;Weyer et al 2001). A number of molecules involved in inflammatory processes have been investigated for their role in type 2 diabetes (Duncan et al 2003;Schmidt et al 1999;Pradhan et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Three specific DNA-protein complexes (bands 1, 2 and 3) and free probes are indicated. The −420G/C variation-independent band is indicated by an asterisk, and the fact that this band is not related to the −420G/C variation was proven in the previous work [21] of resistin in the media was measured using a mouse resistin ELISA kit according to the manufacturer's instructions (Komed, Seoul, Korea) [11].…”
Section: Methodsmentioning
confidence: 96%
“…Levels of resistin expression are similar in normal, insulin-resistant and type 2 diabetic individuals [9]. Recently, however, we observed that plasma resistin levels were elevated in patients with type 2 diabetes compared with those in non-diabetic individuals [11]. Moreover, mice lacking the resistin gene show that resistin plays an important role in the maintenance of blood glucose during fasting, by increasing hepatic glucose production [12].…”
Section: Introductionmentioning
confidence: 94%